Adição de resíduo do extrato aquoso de soja (Okara) em produto tipo hambúrguer formulado com carne bovina - Oliveira, Rafaela Bergmann Strada de (2016)
The search for developing new products has been increasingly explored in the different segments of Brazilian and worldwide agricultural and livestock sectors due to the large variety of available prime matter. Current lifestyle has driven industries to produce new products that be attractive, of easy preparation and that present good flavor and nutritional appeal. The soybean is considered an ally for a healthier lifestyle and generates, in its processing, the okara. This is a byproduct of the production process of the aqueous soybean extract, of which nutritional value presents protein, lipids and fibers in significant amounts, in addition to isoflavones. Large amounts of okara are wasted with its disposal in nature or are destined for animal nutrition. We can change this situation by means of researches that show the feasibility of its use for human feeding. In this sense, a first stage of the present study aimed at evaluating the physical, chemical, microbiological and sensorial characteristics of beef hamburgers with the addition of okara to its humid form. The results showed that the formulations presented better acceptability and technological quality with concentrations of up to 15%. In the second stage of the study, raw and fried hamburgers were evaluated during frozen storage for a period of 120 days. The inclusion of okara was proportional to the decrease in the content of protein, and increase in the content of lipids and humidity of the raw and fried formulations. The inclusion of okara increased the luminosity of the hamburgers, which decreased over storage time. For the raw formulations, at time zero, we observed lower values of b* and a* when compared to the fried hamburgers, which leads to a light brown coloration, indicating the lightening of the color with the increase of okara. The fried hamburgers also presented this indication, however, they were of a darker brown. In conclusion, the formulations were suitable for consumption concerning its satisfactory hygienic-sanitary quality, and the best acceptability and technological quality were observed in the concentrations of up to 15%. After 120 days of storage, the hamburgers met the sugges ted quality of Technical Regulation of Hamburger Identity and Quality regarding the contents of protein, lipids, humidity and the legislation in the microbiological point of view. The brown coloration of the products changed with the inclusion of okara without, however, changing the characteristic coloring of the hamburgers.